2008
DOI: 10.1016/j.resuscitation.2007.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Is the tumour necrosis factor-alpha response following resuscitation gender dependent in the swine model?

Abstract: SummaryIntroduction-Reperfusion results in a proinflammatory cytokine response, as has been observed following resuscitation from cardiac arrest. Variations in the inflammatory response have been shown to be gender dependent and mediated by steroid hormones. The purpose of this study was to determine whether the tumour necrosis factor-alpha response following resuscitation was gender dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
(6 reference statements)
2
10
0
Order By: Relevance
“…We used only male swine in this study due to prior observations suggesting that there are gender differences in the proinflammatory response following resuscitation and that the response is more dramatic and more predictable in males than females. (28) We evaluated one cardiac arrest duration (7 min) prior initiation of resuscitation efforts. A long duration of ischemia may have resulted in a more pronounced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…We used only male swine in this study due to prior observations suggesting that there are gender differences in the proinflammatory response following resuscitation and that the response is more dramatic and more predictable in males than females. (28) We evaluated one cardiac arrest duration (7 min) prior initiation of resuscitation efforts. A long duration of ischemia may have resulted in a more pronounced inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…We used only male swine because previous work has demonstrated that the post-resuscitation inflammatory response in males is more robust than that observed in female swine of similar age. 21 The anesthetics used in this study may affected pre-arrest and post-resuscitation cardiac function and possibly the innate inflammatory response. 23 However, the anesthetic regimen was the same for the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that a systemic inflammatory response follows resuscitation and is characterized by an increase in circulating inflammatory cytokines. 13,13,21 Cytokines, particularly TNF-α, are known to cause myocardial depression by altering calcium homeostasis in myocytes. 22 …”
Section: Discussionmentioning
confidence: 99%
“…25 Male swine were employed in this study due to gender differences in the cytokine response to cardiac arrest observed in this species. 26 It is uncertain whether similar differences exist in human populations. We did not induce hypothermia during the early post-arrest period modeled in this investigation.…”
Section: Discussionmentioning
confidence: 99%